Production Functions with Factor-Oriented Scale Sensitivity - Vijverberg, Chu-Ping C.; Fei, John C. H. (The Review of Economics and Statistics, 1996)
The analysis of economic phenomena at the wholistic (aggregative) level 11l8intains a long tradition that assumes the neoclassical production function Q-f(K,L) (i.e., output as a function of capital and labor) satisfies the condition of constant returns to scale.The assumed absence of any (dis-)economies of scale renders the production function useless, when the scale effect is as pronounced as is typically found at the less aggregative levels of individual firm or industry analvsis.. .The purpose of this paper is to deduce new classes of production functions that are not limited to the constant returns to scale characteristic.Hore specifically, the scale effect is described by an arbitrary function of one of the factors of production, capital in this paper.This class of production functions exhibi-ts scale sensitivity with respect to capital (SSWK).The paper shows how different fmidlies of production functions can be derived from two basic .. building blocks," a :wage share function and a scale functitm.The Cobb-])ouglas, CES and VES production fmu:tions are special cases. e Cobb-Douglas and CES functions can be expanded to incorporate non-constant returns to scale.A smnple of firms from Taiwan is used to test among various derived functional specifications.An interesting diversity of preferred specifications was found among three industries.